2006
DOI: 10.1158/1541-7786.mcr-06-0090
|View full text |Cite
|
Sign up to set email alerts
|

NR0B1 Is Required for the Oncogenic Phenotype Mediated by EWS/FLI in Ewing's Sarcoma

Abstract: A number of solid tumors, such as alveolar rhabdomyosarcoma, synovial sarcoma, and myxoid liposarcoma, are associated with recurrent translocation events that encode fusion proteins. Ewing's sarcoma is a pediatric tumor that serves as a prototype for this tumor class. Ewing's sarcomas usually harbor the (11;22)(q24;q12) translocation. The t(11;22) encodes the EWS/FLI fusion oncoprotein.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
231
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(243 citation statements)
references
References 32 publications
8
231
0
4
Order By: Relevance
“…One of the challenges, however, for identifying which EWS/FLI targets participate in cancer-relevant phenotypes is the complexity of assays required to assess many of these phenotypes, which precludes the development of high-throughput screening approaches. An alternate approach, then, is to limit the number of gene products to be assessed in a lower-throughput screening assays, for example, by comparing microarray profiles across multiple different experiments (Kinsey et al, 2006;Hancock and Lessnick, 2008), or by identifying which genes are 'direct' EWS/FLI targets .…”
Section: Formationmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the challenges, however, for identifying which EWS/FLI targets participate in cancer-relevant phenotypes is the complexity of assays required to assess many of these phenotypes, which precludes the development of high-throughput screening approaches. An alternate approach, then, is to limit the number of gene products to be assessed in a lower-throughput screening assays, for example, by comparing microarray profiles across multiple different experiments (Kinsey et al, 2006;Hancock and Lessnick, 2008), or by identifying which genes are 'direct' EWS/FLI targets .…”
Section: Formationmentioning
confidence: 99%
“…We recently showed that EWS/FLI uses a GGAAmicrosatellite to regulate NR0B1, a gene that is required for oncogenic transformation in Ewing's sarcoma cells (Kinsey et al, 2006;. During the course of these studies, we identified thousands of GGAA-microsatellite-containing genes, suggesting that at least a portion of these might be regulated by direct binding of EWS/FLI to their promoters.…”
Section: Formationmentioning
confidence: 99%
See 3 more Smart Citations